The Real Sector as a Pillar of Economic Stability in Times of Crisis - Safira Elfadhilah; Siti Zailia; KM Badaruddin; Ridho Elrazy (Takaza Innovatix Labs Ltd., 2026)
Global economic crises triggered by financial shocks, pandemics, and geopolitical instability demonstrate that national economies become highly vulnerable when their structural foundations are weak. This study aims to analyze the role of the real sector as a pillar of economic stability during crises using a narrative review approach of eleven relevant studies covering agriculture, MSMEs, the informal sector, real estate, and their linkage with the financial sector. The findings indicate that the real sector is relatively more resilient than other sectors because it sustains production activities, supports domestic consumption, and provides adaptive capacity through flexibility and business diversification. Meanwhile, the financial sector remains important but must operate within policy frameworks that strengthen real economic activities to avoid excessive volatility. These results emphasize that strengthening the real sector, ensuring synergy between fiscal and macroprudential policies, and providing inclusive financial support are essential strategies to build a robust and sustainable national economic resilience.